Challenges in Shariah Audit Practices from the Lense of Practitioners: The Case of Malaysian Takaful Industry - Noor Aimi Mohamad Puad, Zurina Shafii , Nurdianawati Irwani Abdullah (International Journal of Advanced Science and Technology, 2020)
Shariah audit is one of Islamic Financial Institutions’ essential functions as it provides anindependent opinion of the primary purpose of the establishment of Islamic Financial Institutionsas to whether or not the institutions are shariah compliant. Usually, the duties of shariahauditors will be carried out by the internal auditors of each Islamic Financial Institution.However, the effective performance of such duties would depend on the challenges faced by theauditors in conducting shariah audit exercises. Therefore, the main objective of this study is tocritically examine the challenges faced by practitioners in conducting shariah audits and toprovide suggestions to overcome the barriers and attain an effective shariah audit function. Aseries of semi-structured interviews were undertaken with key individuals in Malaysian TakafulOperators who were involved directly and indirectly in the shariah audit process. The keyindividuals include shariah auditors, shariah officers, and shariah committee members. Thefindings of the study highlight the key challenges as described by the practitioners. The studythen proposes solutions to overcome the challenges. The recommendations from the study areuseful in enhancing the current shariah audit practices as well as improving the shariah auditquality.